2007
DOI: 10.1111/j.1365-2214.2007.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of children's weight in a paediatric primary care setting

Abstract: Parents of overweight children frequently did not perceive their children as exceeding healthy weight standards. Targeting parental perception as a point of intervention is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 16 publications
2
50
0
2
Order By: Relevance
“…One of the reasons cited for this growing trend is the failure of parents to recognize that their child is overweight or obese (Huang et al, 2009;Wald et al, 2007;West et al, 2008). Parental awareness of and concern that their child's weight is above the healthy range is inherent in the success of any obesity prevention intervention (Rhee et al, 2005;Wald et al, 2007) and is a significant reason why parents decline to participate in obesity reduction interventions (Taveras et al, 2010). In this study, we demonstrate that many minority, lowincome caregivers cannot use the CDC BMI Growth Chart to identify their child's weight status, the instrument commonly used by pediatricians to characterize a child's weight status (Ariza et al, 2009;Dilley et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons cited for this growing trend is the failure of parents to recognize that their child is overweight or obese (Huang et al, 2009;Wald et al, 2007;West et al, 2008). Parental awareness of and concern that their child's weight is above the healthy range is inherent in the success of any obesity prevention intervention (Rhee et al, 2005;Wald et al, 2007) and is a significant reason why parents decline to participate in obesity reduction interventions (Taveras et al, 2010). In this study, we demonstrate that many minority, lowincome caregivers cannot use the CDC BMI Growth Chart to identify their child's weight status, the instrument commonly used by pediatricians to characterize a child's weight status (Ariza et al, 2009;Dilley et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Parents need to identify their children's weight problems and understand the accompanying short and long-term risks and they look to their pediatricians for advice and guidance (Hernandez et al, 2010). But parents and pediatricians often underestimate children's body size (Akerman et al, 2007;Chaimovitz et al, 2008;Jones et al, 2011;Lampard et al, 2008;Parry et al, 2008;Perrin et al, 2005;Spurrier et al, 2006;Tschamler et al, 2010;Wald et al, 2007). Unrecognized obesity is especially high for obese parents, for overweight as compared to obese children (Taveras et al, 2011), for lower socioeconomic parents (Rivera-Soto and Rodriguez-Figueroa, 2012) and for Hispanics (Intagliata et al, 2008), African Americans (West et al, 2008) and Native Americans (Arcan et al, 2012) and could impair parental motivation to adopt weight control measures (Vuorela et al, 2010) and to participate in obesity reduction programs (Taveras et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Parents of older children presented higher levels of concern about eating, sleep and physical complaints. Wald et al (2007) reported that parental perceptions about their children's overweight were more often correct for parents of older children, when compared to those of younger children.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura aponta a existência de associação entre o sexo da criança e a percepção materna do estado nutricional do filho, evidenciando que os pais não reconhecem o excesso de peso nos meninos e o baixo peso nas meninas, o que significa que os pais subestimam o peso dos meninos e superestimam o peso das meninas 46,60,63,69,72,77,78,82,86 .…”
Section: Descrição Dos Resultados Obtidos Sobre As Adequações De Percunclassified
“…Resultados: A concordância entre a percepção materna e da autopercepção nutricional da criança com o estado nutricional real da criança é pobre (Kappa ponderado 0,236 e 0,295 respectivamente). 50 63, p<0,001). As meninas tendem a superestimar o próprio estado nutricional e os meninos tendem a subestimar (p=0,027).…”
Section: Bvsunclassified